Integrating Multicultural Values to Foster Tolerance and Inclusivity in Islamic Religious Education - Muhajir Muhajir; Umi Kultsum; Moh. Miftachul Choiri; Siti Mustonah; Heramb Kulkarni; Abdul Karim (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2025)
Multicultural education plays a vital role in enhancing religious tolerance within Islamic Religious Education (IRE), particularly in Indonesia, where religious exclusivism and intolerance remain ongoing challenges. The objective of this research was to explore the understanding and application of multicultural values in Islamic Religious Education among junior high school and madrasa students. A mixed-method approach was utilized, combining qualitative and quantitative analysis to gain a comprehensive understanding of the issue. Through open-ended interviews and surveys, data were collected from students in two junior high schools in Cilegon and one madrasa in Serang, Indonesia. The qualitative data were analyzed using a descriptive-exploratory approach, while quantitative data were analyzed with descriptive statistics. The study found that integrating religious education with multicultural values fostered a strong sense of interfaith tolerance, cultural appreciation, and inclusivity. This integration helped students embrace diversity, respect differences, and build mutual trust, thereby minimizing conflicts and promoting a harmonious learning environment. The findings underscore the significance of effective multicultural education in shaping an inclusive Islamic education system, ultimately enhancing both the social and academic outcomes of students in Indonesia.